The subsnance nouns with -v- suffix and its allomorphes in Russian language: the diachronic aspekt - Solodkaya, Oxana I. (Journal of the Belarusian State University. Philology, 2020)
The history of substance nouns with the -v- suffix and its allomorphs in Russian language is considered. The purpose of the article is to determine the degree of productivity of the type of formation of substance nouns with the -v- suffix on different periods of time, as well as to characterize the derivational structure of the studied words with the definition of the semantic and grammatical features of the generating basis. On the basis of data from etymological dictionaries, as well as derivational and lexical analysis of material substances formed with the -v- suffix, it was established the following: a decrease in the degree of productivity of the word-formation type under consideration in the direction from the Proto-Slavic period to the modern linguistic state; the predominance of verbal generative bases; the phenomenon of synonymous competition with suffixes -n-, -l-, -j-, -k- or their allomorphs; the thematic classification of the considered substances is given; the phenomenon of the loss of polysemy by nouns with a material meaning in the literary language, while retaining it in dialects, was established.